Pengolahan dan Manajemen Usaha Produk Camilan Keripik Ikan Mujair dalam Upaya Meningkatkan Potensi Lokal - Ziecky Mardoni (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2021)
The purpose of the Community Service Program for the Utilization of Science and Technology for the Community of Solok City, Kel IX Korong, is to provide training and assistance on processing and business management to the